ANALYSIS OF CAPITAL MARKET REACTION BEFORE AND AFTER SUSTAINABILITY REPORTING AWARD - Lindawati, Ang Swat Lin; Setyaningrum, Sandra; Mulyawan, Archie Nathanael; Meiryani, Meiryani (Journal of Applied Finance and Accounting, 2023)
The attention of investors and potential investors to environmental and economic reporting social issues is increasing along with the number of environmental cases that occur in Indonesia. Companies that win the Indonesia Sustainability Reporting Award will boost the company's image in the eyes of the public because it has won an award which prioritizes harmony between economic, social and environmental aspects. The purpose of this study was to analyze the reaction of the capital market before COVID-19 in companies that Achieved the Sustainability Reporting Award around the announcement date Sustainability Reporting Award in 2015-2019 (the period before COVID-19), measured using abnormal return and trading volume activity. This study will provide data and information regarding the capital market reaction period before covid 19 which it will use for further research related to the efficiency capital market hypothesis. The period that is used in this research is D-5 (before the announcement) and D + 5 (after the announcement). This study used the data from Yahoo Finance Secondary, such as adjusted closing stock price and closing price of JCI. Samples were selected by purposive sampling method so that the samples Obtained were 53 companies. The analytical method used in this observation is a paired sample t-test using SPSS 20 software. The results of this study indicate that there are no significant differences in abnormal return and trading volume activity between the period prior and the period after the announcement.